Романтизм і український гранд–наратив - Ясь, О. (Інститут історії України НАН України, 2008)
Highlightened is the role of romanticism in formation of the Ukrainian grand-narrative. Regarded is transformation of the cultu ral field, in particular establishment of a new public space in Russian Empire in the first half of the 19th century, in capacity of a system factor of the Ukrainian historiography creation. Suggested is the fact that romanticism / neoromanticism triggered several legitimate projects of a «discovery» of Ukraine.